EKSISTENSI TOKOH UTAMA SEBAGAI PEREMPUAN JAWA DALAM NOVEL NAWUNG KARYA GALUH LARASATI: TINJAUAN FEMINISME EKSISTENSIALIS - Nur Lailatulul Qadriani; St. Mutmainnah Ihsan; Mustika Mustika (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2022)
The purpose of this study is to describe the existence of the main character as a Javanese woman in the novel Nawung by Galuh Larasati. To find out the existence of the main character, this research uses the feminist existentialist proposed by Simone De Beauvoir. The method in this research is descriptive qualitative analysis. The results of this study indicate that; 1) the main character is a Javanese woman who is labeled as intellectual; 2) the main character is a Javanese woman who works, and pursues many professions; 3) the main character is a Javanese woman who achieves social transformation, becomes an agent of change in her area by establishing a mini library since childhood, establishing a school for underprivileged children, and turning her village garden into a large natural park; and 4) the main character as a Javanese woman who refuses to be someone else, but independent and free to determine her own future.